2013
DOI: 10.1186/2047-2994-2-3
|View full text |Cite
|
Sign up to set email alerts
|

From intermittent antibiotic point prevalence surveys to quality improvement: experience in Scottish hospitals

Abstract: BackgroundIn 2008, the Scottish Antimicrobial Prescribing Group (SAPG) was established to coordinate a national antimicrobial stewardship programme. In 2009 SAPG led participation in a European point prevalence survey (PPS) of hospital antibiotic use. We describe how SAPG used this baseline PPS as the foundation for implementation of measures for improvement in antibiotic prescribing.MethodsIn 2009 data for the baseline PPS were collected in accordance with the European Surveillance of Antimicrobial Consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…There are well-established surveillance methodologies developed by The European Surveillance of Antimicrobial Consumption (ESAC) Project but these PPSs have focused mainly on adults [9]. PPSs have been used in hospitals not only at the European level but also undertaken at the national and individual hospital level [10,11]. There are some studies on antibiotic use in pediatric population using PPSs [12] but methodology was adopted from adult PPSs and it was not specifically designed for children.…”
Section: Introductionmentioning
confidence: 99%
“…There are well-established surveillance methodologies developed by The European Surveillance of Antimicrobial Consumption (ESAC) Project but these PPSs have focused mainly on adults [9]. PPSs have been used in hospitals not only at the European level but also undertaken at the national and individual hospital level [10,11]. There are some studies on antibiotic use in pediatric population using PPSs [12] but methodology was adopted from adult PPSs and it was not specifically designed for children.…”
Section: Introductionmentioning
confidence: 99%
“…PPSs can be a successful method to monitor trends in antibiotic prescribing and identify targets for quality improvement 9. PPSs are an important tool for a quality control exercise because they provide useful data for targeted interventions and further study 22.…”
Section: Discussionmentioning
confidence: 99%
“…Well-established surveillance methodologies were developed by the European Surveillance of Antimicrobial Consumption (ESAC) Project, but these have focused mainly on adults7 with only some studies carried out in the paediatric population 8. PPSs have been undertaken in hospitals at the individual, national and European level 9 10…”
Section: Introductionmentioning
confidence: 99%
“…The collection of prevalence data in 2009 led to the development of two quality prescribing indicators: (1) the extent of compliance with antibiotic policies among acute admission units and (2) surgical prophylaxis duration (Malcolm et al 2013). The collection of prevalence data in 2009 led to the development of two quality prescribing indicators: (1) the extent of compliance with antibiotic policies among acute admission units and (2) surgical prophylaxis duration (Malcolm et al 2013).…”
Section: Hospitalsmentioning
confidence: 99%
“…The collection of prevalence data in 2009 led to the development of two quality prescribing indicators: (1) the extent of compliance with antibiotic policies among acute admission units and (2) surgical prophylaxis duration (Malcolm et al 2013). Overall, SAPG has shown that the implementation of national prescribing indicators, which are acceptable to clinicians and regularly audited, can improve subsequent antibiotic utilisation (Malcolm et al 2013). Following the implementation of prescribing indicators, there was an improvement in the indication noted in the patient records of 90 %.…”
Section: Hospitalsmentioning
confidence: 99%